Approaching postmodernism : papers presented at a Workshop on Postmodernism, 21-23 September 1984, University of Utrecht - Fokkema, Douwe Wessel, 1931-2011; Bertens, Johannes Willem (Benjamins, 1986)
Most of the essays collected in this volume deal with theoretical issues that dominate the international debate on Postmodernism, issues such as the shifting nature of the concept, the problem of periodization and the problem of historicity. Other essays offer readings of Postmodernist texts and relate practical criticism to a theoretical framework. Hans Bertens (Utrecht) sketches the historical development of the concept Postmodernism in American criticism, distinguishing between the various definitions that have been proposed over the last twenty-five years, in an attempt to bring some order.
Keywords: Literature, Modern -- 20th century -- History and criticism -- Congresses.; Postmodernism (Literature) -- Congresses.; Postmodernism -- Congresses.; Littérature -- 20e siècle -- Histoire et critique -- Congrès.; Postmodernisme -- Congrès.; Postmodernisme (Littérature) -- Congrès.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Postmodernism; Literature, Modern; Postmodernism (Literature); Literatuurwetenschap.; Postmodernisme.; 1900-1999; Conference papers and proceedings; Criticism, interpretation, etc.